Biosurfactant-enriched organic fertilizer as a sustainable strategy to reduce chemical inputs and improve maize performance on Ultisols - Jamilah Jamilah; Khairul Effendi; Sunadi Sunadi; Widodo Haryoko; M. Zulman Harja Utama; Nur Qursyna Boll Kassim (Universitas Sebelas Maret, 2025)
The increasing demand for maize in Indonesia is challenged by suboptimal productivity on acidic Ultisols, despite high doses of inorganic fertilizers being applied. This study aimed to evaluate soil pH dynamics and maize response to liquid organic fertilizer (LOF) enriched with Sapindus rarak biosurfactants as a substitute for chemical fertilizers. A factorial completely randomized design was used with two factors: inorganic fertilizer (NPK + Urea) doses (0%, 50%, and 100% of the recommended rate) and biosurfactant concentrations (0%, 0.1%, 0.2%, and 0.3%). Data were analysed using the F-test at a 5% significance level, with LSD tests applied for significant effects. Results showed that soil pH in maize crops decreased over time but remained slightly acidic. Higher NPK doses generally increased soil pH, especially at 45 days after planting (DAP). Biosurfactant-enriched LOF significantly impacted leaf area index (LAI), relative growth rate (RGR), and shoot-root ratio, particularly at 60 DAP. The highest maize yield, reaching 6.60 tons per hectare, was obtained with a combination of 50% of the recommended inorganic fertilizer and 50 mL L⁻¹ of 0.1% biosurfactant-enriched LOF. This yield is comparable to the normal yield obtained by farmers when applying 100% of the recommended rate of inorganic fertilizer. Optimising fertilizer application and planting strategies to effectively manage the shoot-to-root ratio is essential for improving maize productivity and enhancing resource use efficiency. The study highlights the potential to reduce chemical fertilizer use by up to 50%, lowering costs while improving soil pH and root development. It promotes efficient resource use, supports integrated nutrient management using local materials such as Sapindus rarak, and encourages farmer training and sustainable agricultural policies to restore productivity on degraded Ultisols.